Militias as a Tool for Encouraging Ethnic Defection: Evidence from Iraq and Sudan - Voller, Yaniv (Terrorism and political violence, 2023)
Ethnic defection and pro-government militias are two recurring features of ethnic conflicts. There is a strong connection between these two elements, with incumbents using militias to absorb defectors from rebel constituencies into their ranks. However, relatively little work has been carried out on this link. Most works exploring ethnic defection have treated these defector militias, as the article refers to them, as the result of ethnic defection. This research offers an alternative hypothesis: Rather than tools for administrating and controlling defection, governments in ethnic civil wars often view militias as a tool for enhancing and facilitating ethnic defection. The socio-political functions of militias may triumph over military ones in governments’ consideration to form and sustain such defector militias. The article employs two case studies to support this hypothesis, these of the ethnic conflicts in northern Iraq and southern Sudan.